Low peer acceptance and emotional/behavioural maladjustment in schoolchildren: Effects of daily stress, coping and sex - Escobar, Milagros; Fernández Baena, Francisco Javier; Miranda, Jesús; Trianes, María Victoria; Cowie, Helen (Anales de Psicología / Annals of Psychology, 2011)
This study examines the relationship between low peer accep-tance and emotional/behavioural maladjustment, taking into account the effects of daily stress, coping styles and sex. The sample comprised 392 schoolchildren (187 females and 205 males) aged 9 to 12, to whom a peer rating scale was administered. Self-report measures of perceived daily stress, coping and emotional/behavioural maladjustment were also ap-plied. Regression analysis indicated that daily stress, coping and sex were significant predictors of emotional/behavioural maladjustment, after controlling for peer acceptance. These results provide evidence about underlying factors that could help in understanding the development of emotional/behavioural problems in children with low peer acceptance.